AI in Special Education: Balancing Technical Potential with Ethical and Practical Realities - Catama, Bryan V (International Journal of Rehabilitation and Special Education (IJRSE), 2026)
As artificial intelligence (AI) becomes more prominent in education, its role in  special education is increasingly defined by the tension between technological  potential and implementation realities. This narrative review synthesizes 13 studies  published between 2022 and 2025 to examine how recent scholarship positions AI  and large language models (LLMs) in inclusive and special education. The review  identifies a growing shift toward AI-based identification of neurodevelopmental  disorders through pattern recognition and digital biomarkers. It also highlights real time personalization, with AI adapting curriculum delivery to students’ cognitive  and emotional needs to support diverse learners. In addition, AI shows promise in  reducing teacher workload by automating administrative tasks, including the drafting  and monitoring of Individualized Education Programs (IEPs). At the same time,  the literature raises concerns about pedagogical displacement, algorithmic bias, and  the tension between data surveillance and cognitive liberty. These ethical issues are  compounded by practical limitations, particularly the lack of longitudinal evidence and  the geographic imbalance in existing research, which may deepen inequities in low resource settings. The review suggests that AI should function as a multidisciplinary  support tool that preserves the professional judgment and relational foundations of  human-centered pedagogy.
Keywords: Artificial Intelligence; Special Education; Inclusive Education; N e u r o d e v e l o p m e n t a l Disorders; Ethics; Personalized Learning